CO2 measurement protocol to determine the minimum amount of soil and litter samples - Barrales-Brito, Edgar; Paz-Pellat, Fernando; Etchevers-Barra, Jorge D.; Hidalgo-Moreno, Claudia; Velázquez-Rodríguez, Alma S. (REVISTA TERRA LATINOAMERICANA, 2022)
Soil organic matter (SOM) and its interaction with elementary soil particles (ESP) determine mineralization rates. Thus quantifying how much CO2 is released by soil elementary fractions is necessary. However, in the fractionation methods of ESP a very small amount is extracted limiting incubation tests with traditional methods, which require quantities of 30 g to make measurements in the laboratory. Tests were conducted to determine if the OxiTop equipment is capable of measuring the respiration of soil samples in small quantities of 10.0, 5.0, 1.0 and 0.5 g of litter samples (M), fermentation horizon (HF) and soil (S) in 500 and 250 mL equipment bottles. The results show that the equipment records the amount of CO2 in all the samples, which are greater in M than in S samples. In addition, the bottle size indicated that the respiration is proportional to size since in the 500 mL bottles the CO2 amount was nearly double compared to the 250 mL bottles in M and HF samples. In S samples the values measured in both bottles were very similar. The OxiTop equipment is able to measure CO2 emission in small samples. Nevertheless, the C content of the sample inf luenced the results, when the C contents are low the amount of CO2 is lower.